Rapid and Stable Recovery Method in Re-adhesion for High-cold EMUs - ZHANG Liwei; YU Lizhi; ZHANG Zhengfang (机车电传动)
The bad operation environment of the high-speed EMUs is a big challenge to adhesion control of the rail between the wheel and rail. A method of rapid and stable recovery method in re-adhesion for high-cold EMUs was proposed, which could ensure the smooth operation of the EMUs in the severe freezing weather, the comfort level, and the maximum utility of the adhesion between the wheel and rail to ensure the punctuality of the EMUs. Through the experimental in the high-cold EMUs line, the actual running data showed that the method could reduce the chance of second slip/slide of EMUs in the case of the maximum available adhesion of the wheel and rail.